The Role of Place-Names in Preserving Living Heritage in Matabeleland - Moyo, Mthokozisi (2022)
This paper focuses on the role of indigenous place- names in Matabeleland as a way of preserving living heritage. Names serve an important function of connecting us with our environment and the cosmos. They connect us with our spirit world, physical natural and the built environments, thus they and should be preserved as part of our oral history and cultural heritage. Earlier toponomastics research done in Bulawayo and the surrounding areas of Matabeleland has focused more on the linguistic modelling and the etymology of these names without attention to the role of names in the preservation aspect of living heritage. Using the New Convergence Theory the study advances the idea that indigenous place-names are key in preserving living heritage, particularly wildlife as a form of living heritage. By focusing on the intersections between toponyms and wildlife within selected Matabeleland communities in Zimbabwe, this article analyses and bring to the fore how the abundant wildlife informs the place-naming in both rural and urban contexts